Pengaruh Aktivitas Bisnis Terhadap Nilai Perusahaan - Lilik Mardiana; Wiwin Wahyuni; Sukamto Sukamto (Research Institution and Community Service Universitas Wijaya Kusuma Surabaya, 2022)
The purpose of research is to analyze the impact of business activities on firms in terms of working capital, receivables, and fixed assets. A manufacturing company listed on the Indonesian Stock Exchange. The population of this study was that of several manufacturing companies listed on the Indonesian Stock Exchange, and the sample was selected for inclusion based on data meeting 92 criteria. We used a randomized approach and regression analysis. The results show that working capital turnover, accounts receivable turnover and fixed assets turnover together affect the value of a company. But in reality, only part of the working capital has a significant impact on the company, while accounts receivable and fixed assets have no impact on the company's production. This is the first indication that companies that manage their operations (working capital in circulation) well have an impact on their share prices.